Fumarate respiration of Fasciola flukes as a potential drug target - Tashibu, Atsushi; Inaoka, Daniel Ken; Sakamoto, Kimitoshi; Murakami, Kenji; Zannatul, Ferdoush; Kita, Kiyoshi; Ichikawa-Seki, Madoka (Frontiers in Cellular and Infection Microbiology, 2024)
Fascioliasis is a neglected tropical zoonotic disease caused by liver flukes belonging to the genus Fasciola. The emergence of resistance to triclabendazole, the only World Health Organizationrecommended drug for this disease, highlights the need for the development of new drugs. Helminths possess an anaerobic mitochondrial respiratory chain (fumarate respiration) which is considered a potential drug target. This study aimed to evaluate the occurrence of fumarate respiration in Fasciola flukes. We analyzed the properties of the respiratory chain of Fasciola flukes in both adults and newly excysted juveniles (NEJs). Fasciola flukes travel and mature through the stomach, bowel, and abdominal cavity to the liver, where oxygen levels gradually decline. High fumarate reductase activity was observed in the mitochondrial fraction of adult Fasciola flukes. Furthermore, rhodoquinone-10 (RQ10 Em'= -63 mV), a low-potential electron mediator used in fumarate respiration was found to be predominant in adults. In contrast, the activity of oxygen respiration was low in adults. Rotenone, atpenin A5, and ascochlorin, typical inhibitors of mitochondrial enzymes in complexes I, II, and III, respectively, inhibit the activity of each enzyme in the adult mitochondrial fraction. These inhibitors were then used for in vitro viability tests of NEJs. Under aerobic conditions, NEJs were killed by rotenone or ascochlorin, which inhibit aerobic respiration (complex I-III), whereas atpenin A5, which inhibits complex II involved in fumarate respiration, did not affect NEJs. Moreover, ubiquinone-10 (UQ10 Em'= +110 mV), which is used in oxidative respiration, was detected in NEJs, in addition to RQ 10. In contrast, under anaerobic conditions, rotenone and atpenin A5, which inhibit fumarate respiration (complex I-II), were crucial for NEJs. These findings demonstrate that NEJs have active hybrid respiration, in which they can properly use both oxygen and fumarate respiration, depending on oxygen availability. Thus, fumarate respiration is a promising drug target for Fasciola flukes, because it plays an essential role in both adults and NEJs.